Behavioral Characterization of β-Arrestin 1 Knockout Mice in Anxiety-Like and Alcohol Behaviors - Robins, Meridith T.; Chiang, Terrance; Berry, Jennifer N.; Ko, Mee Jung; Ha, Jiwon E.; van Rijn, Richard M. (Frontiers in Behavioral Neuroscience, 2018)
β-Arrestin 1 and 2 are highly expressed proteins involved in the desensitization of G protein-coupled receptor signaling which also regulate a variety of intracellular signaling pathways. Gene knockout (KO) studies suggest that the two isoforms are not homologous in their effects on baseline and drug-induced behavior; yet, the role of β-arrestin 1 in the central nervous system has been less investigated compared to β-arrestin 2. Here, we investigate how global β-arrestin 1 KO affects anxiety-like and alcohol-related behaviors in male and female C57BL/6 mice. We observed increased baseline locomotor activity in β-arrestin 1 KO animals compared with wild-type (WT) or heterozygous (HET) mice with a sex effect. KO male mice were less anxious in a light/dark transition test, although this effect may have been confounded by increased locomotor activity. No differences in sucrose intake were observed between genotypes or sexes. Female β-arrestin 1 KO mice consumed more 10% alcohol than HET females in a limited 4-h access, two-bottle choice, drinking-in-the-dark model. In a 20% alcohol binge-like access model, female KO animals consumed significantly more alcohol than HET and WT females. A significant sex effect was observed in both alcohol consumption models, with female mice consuming greater amounts of alcohol than males relative to body weight. Increased sensitivity to latency to loss of righting reflex (LORR) was observed in β-arrestin 1 KO mice although no differences were observed in duration of LORR. Overall, our efforts suggest that β-arrestin 1 may be protective against increased alcohol consumption in females and hyperactivity in both sexes.